2008
DOI: 10.1177/0146167208324512
|View full text |Cite
|
Sign up to set email alerts
|

Getting Off on the Wrong Foot: The Timing of a Breach and the Restoration of Trust

Abstract: Few interpersonal relationships endure without one party violating the other's expectations. Thus, the ability to build trust and to restore cooperation after a breach can be critical for the preservation of positive relationships. Using an iterated prisoner's dilemma, this article presents two experiments that investigated the effects of the timing of a trust breach-at the start of an interaction, after 5 trials, after 10 trials, or not at all. The findings indicate that getting off on the wrong foot has deva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 51 publications
6
120
1
Order By: Relevance
“…Past research has largely focused on the role of situational factors, such as emotion (Dunn & Schweitzer, 2005;Lount, 2010), social status (Lount & Pettit, 2011), and timing of the trust breach (Lount et al, 2008) to predict trust restoration. Our research shows that gender is one important personal characteristic that influences trust recovery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Past research has largely focused on the role of situational factors, such as emotion (Dunn & Schweitzer, 2005;Lount, 2010), social status (Lount & Pettit, 2011), and timing of the trust breach (Lount et al, 2008) to predict trust restoration. Our research shows that gender is one important personal characteristic that influences trust recovery.…”
Section: Discussionmentioning
confidence: 99%
“…We extend our investigation in Study 2 by considering trust following a different untrustworthy experience. Prior work (e.g., Lount et al, 2008) has found that the timing of a relationship breaches matters. Whereas participants in Study 1 experienced a relationship that was initially trustworthy followed by an untrustworthy episode, in Study 2 participants are initially exposed to a counterpart's untrustworthy actions, followed by an attempt to rebuild trust.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Repeated trust games have been used to study trust building (Pillutla, Malhotra, and Murnighan 2003;Ho and Weigelt, 2005) and trust repair (Schweitzer, Hershey, and Bradlow 2006;Kim, Dirks, Cooper, and Ferrin 2006;Lount, Zhong, Sivanathan and Murnighan 2008). In our studies, we use a repeated trust game to study the influence of monitoring.…”
Section: Literature Review Experimental Studies Of Trustmentioning
confidence: 99%